BCG vaccination at birth and early childhood hospitalisation: a randomised clinical multicentre trial. Issue 3 (21st July 2016) - Stensballe, Lone Graff; Sørup, Signe; Aaby, Peter; Benn, Christine Stabell; Greisen, Gorm; Jeppesen, Dorthe Lisbeth; Birk, Nina Marie; Kjærgaard, Jesper; Nissen, Thomas Nørrelykke; Pihl, Gitte Thybo; Thøstesen, Lisbeth Marianne; Kofoed, Poul-Erik; et al.
Abstract : Background: The BCG vaccine is administered to protect against tuberculosis, but studies suggest there may also be non-specific beneficial effects upon the infant immune system, reducing early non-targeted infections and atopic diseases. The present randomised trial tested the hypothesis that BCG vaccination at birth would reduce early childhood hospitalisation in Denmark, a high-income setting. Methods: Pregnant women planning to give birth at three Danish hospitals were invited to participate. After parental consent, newborn children were allocated to BCG or no intervention within 7 days of age. Randomisation was stratified by prematurity. The primary study outcome was number of all-cause hospitalisations analysed as repeated events. Hospitalisations were identified using The Danish National Patient Register. Data were analysed by Cox proportional hazards models in intention-to-treat and per-protocol analyses. Results: 4184 pregnant women were randomised and their 4262 children allocated to BCG or no intervention. There was no difference in risk of hospitalisation up to 15 months of age; 2129 children randomised to BCG experienced 1047 hospitalisations with a mean of 0.49 hospitalisation per child compared with 1003 hospitalisations among 2133 control children (mean 0.47), resulting in a HR comparing BCG versus no BCG of 1.05 (95% CI 0.93 to 1.18) (intention-to-treat analysis). The effect of BCG was the same in children born at term (1.05 (0.92 to 1.18)) and prematurely (1.07 (0.63 to 1.81), p=0.94). The effect was also similar in the two sexes and across study sites. The results were essentially identical in the per-protocol analysis and after adjustment for baseline characteristics. Conclusions: BCG vaccination at birth did not reduce the risk of hospitalisation for somatic acquired disease until 15 months of age in this Danish study population. Trial registration number: NCT01694108, results.